Research Delays toward Research Ecosystem Development: A Systemic Analysis in the Context of Prince of Songkla University, Pattani Campus - Sares, Alisa; Senman, Santi (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study aims to investigate the factors, compare the differences, and analyze the systemic relationships contributing to research delays; explain the complex mechanisms of these delays through the balance of job demands and resources using the Job Demands-Resources (JD-R) Model; and propose guidelines for developing a research ecosystem in higher education institutions to promote timely research completion. A mixed-methods design was employed. Data were collected from academic staff and researchers at Prince of Songkla University, Pattani Campus, who received internal research funding between 2017 and 2024, using structured questionnaires and in-depth interviews. Quantitative findings reveal that all contributing factors were significantly and positively interrelated, indicating a systemic pattern of research delay. A particularly strong association was identified between research process factors and research outcome factors. No statistically significant differences were found across gender, educational level, or academic rank; however, prior experience in receiving internal research funding emerged as a significant determinant shaping researchers’ perceptions of obstacles, specifically in relation to personal and funding-condition factors. Qualitative findings further confirm that research delays should not be attributed solely to individual limitations but reflect a systemic imbalance between academic workload, inflexible administrative regulations, and productivity pressures that exceed available institutional resources. The study therefore proposes the development of a research ecosystem framework that shifts institutional emphasis from document-centered compliance toward process-based research support, including academic mentorship and workload reduction, to create an environment conducive to successful and timely research completion in higher education institutions.